La Armonización De Los Impuestos Indirectos Según Las Decisiones 599 Y 600 De La Comunidad Andina - Caller Ferreyros, María E. (Revista de Derecho, 2019)
Decisions 599 and 600, were issue by the Andean Commission on 12 July 2004 and came into effect on 01 January 2008. Such Decisions, whose legal validity has been recognized by the Andean Community Court, have as their object to achieve harmonization of the legislation of member countries of the Andean Community –Perú, Colombia, Ecuador and Bolivia- which regulate aggregate value type and consumption taxes, in the hopes that such imposition is neutral, that economic integration is facilitated and that restrictions to intra-communitarian commerce are eliminated. For such effect, it is required that member countries comply with the transposition to national law of the guidelines of indirect imposing foreseen by the quoted Decision, because, even when the principles of pacta sun servanda and the supremacy of international law over internal law determine that treaties prevail over internal norms with the range of laws, normative changes that are required in our country to implement Decision 599, should observe the constitutional principle of law reserve foreseen in article 74 of the Constitution. It is of upmost importance to know about the scope of Decisions 599 and 600, as well as the aspects whose regulation differ in relation to the Law of General Sales Taxes and Consumption which governs our country. This will allow for the identification of normative changes that the implementation of such Decisions should require, and when facing non-compliance from part of the State, the effects this will generate in the tax payers, who will be able to call for the direct application of the Decisions in those aspects which favor them (estoppel).